Stability-Indicating Methods for NSAIDs in Topical Formulations and Photoprotection in Host-Guest Matrices - Ioele, Giuseppina; Tavano, Lorena; Muzzalupo, Rita; De Luca, Michele; Ragno, Gaetano (Mini Reviews in Medicinal Chemistry, 2016)
Photostability tests applied on topical commercial formulations containing non-steroidal anti-inflammatory drugs have demonstrated a clear degradation of the active compounds when exposed to light. The photodegradation profile of these drugs is usually monitored by spectrophotometric or chromatographic techniques according to the international ICH rules for photostability testing. In the last years, the data are processed ever more by multivariate analysis, as principal component analysis, partial least squares, multivariate curve resolution. These techniques have proved to be able to resolve the complex data sets from evolving chemical processes, by estimating the number of the involved components, their pure spectra and concentration profiles. When applied to the study of drug photodegradation, the multivariate approach has been able to define completely the reaction mechanisms and kinetics parameters. Several novel pharmaceutical formulations have been described to improve the photostability of NSAIDs in topical formulations. The common use of light protective packaging has recently been replaced or supplemented by incorporating suitable excipients in the drug formulations. The addition of UV absorbent agents, deactivating quench reactions that are either singlet oxygen-driven or involve free radicals, has had good success. A clear improvement in the light protection has been shown by entrapping the drugs into supramolecular matrices as cyclodextrins, liposomes, niosomes and other host-guest matrices. The present review gives an updated overview on the stability-indicating methods adopted for a series of NSAIDs in topical formulations and the supramolecular matrices designed to minimize the drug photodegradation.
Keywords: liposomes